Analisis Risiko dalam Implementasi Business Process Management - Jeni Susyanti; Haifatul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Business Process Management is a systematic approach to improving the efficiency and effectiveness of business processes. However, implementation is not free from various risks that can hinder the achievement of organizational goals. This article aims to analyze various risks that arise during the BPM implementation process, including technical, organizational and human risks. This research uses a qualitative approach with literature studies and in-depth interviews with several companies that have implemented . The results of the analysis show that the most dominant risks come from a lack of top management involvement, employee resistance, and information technology system incompatibility. The implications of this study provide important insights into planning and mitigating risks in future BPM projects.